INSTITUTIONAL PRESSURES AND STRATEGIC RESPONSIVENESS: EMPLOYER INVOLVEMENT IN WORK-FAMILY ISSUES. - GOODSTEIN, J. D. (Academy of Management Journal, 1994)
Organizational scholars are increasingly conceptualizing organizational responsiveness to institutional pressures as a strategic choice. This research identified a number of important institutional...